Identification of predictors for wound complications following preoperative or postoperative radiotherapy in extremity soft tissue sarcoma. Issue 6 (June 2018) - Stevenson, Marc G.; Ubbels, Jan F.; Slump, Jelena; Huijing, Marijn A.; Bastiaannet, Esther; Pras, Elisabeth; Hoekstra, Harald J.; Been, Lukas B.
Abstract: Introduction: In extremity soft tissue sarcoma (ESTS), external beam radiotherapy (EBRT) has been used in addition to limb-sparing surgery (LSS). This study aims to identify predictors for major wound complication (MWC) development following EBRT and LSS in ESTS. Methods: This retrospective study includes ESTS patients treated with EBRT and LSS between 2005 and 2017. Two groups were formed; Group I included preoperatively irradiated patients, whereas Group II included patients who underwent postoperative EBRT. Multivariate logistic regression analyses were performed to create a prediction model for MWC development. Results: One hundred twenty-seven patients were included, 58 patients (45.7%) in Group I and 69 patients (54.3%) in Group II. Some differences in baseline characteristics were found between the groups, e.g. in tumor size and grade, histological subtype and total RT dose. Twenty-three patients (39.7%) in Group I and 14 patients (20.3%) in Group II developed a MWC (p = 0.02). Preoperative EBRT was identified as independent predictor for MWC development, OR 2.75 (95%CI 1.21–6.26), p = 0.02. Furthermore, a trend towards an increased MWC risk was shown for patients' age (OR 1.02 (0.99–1.04)), delayed wound closure (OR 3.20 (0.64–16.02)) and negative surgical margins (OR 2.26 (0.72–7.11)). The area under the curve (AUC) of the model was 0.68 (0.57–0.79). Conclusions: This study corroborates the increased MWC risk following preoperative EBRT in ESTS. It remains important to carefully weigh the MWC risk against the expected long-term functional outcome, and to consider the liberal use of primary plastic surgical reconstructions in an individualized multidisciplinary tumor board prior to treatment.